2015
DOI: 10.1208/s12249-015-0357-2
|View full text |Cite
|
Sign up to set email alerts
|

Melt-Extruded Eudragit® FS-Based Granules for Colonic Drug Delivery

Abstract: Abstract. The purpose of this study is to characterize the properties of Eudragit® FS-based granules prepared using melt extrusion process for colonic drug delivery. 5-Aminosalicylic acid (5-ASA), theophylline, and diclofenac sodium were used as the model compounds. Drug and polymer blends were meltextruded into thin rods using a single screw extruder. Drugs were found to be dispersed as crystalline particles in the granules. A hammer mill was used to reduce the extrudate into 16-40 mesh granules, which were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This is attributed to the increased surface area due to the smaller particle size of the powdered formulation. Sustained drug release from the larger pellet size could be attributed to either the lower surface area of the larger pellets compared to the smaller pellets or increased average distance for diffusion of the active ingredient from the pellet (33).…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the increased surface area due to the smaller particle size of the powdered formulation. Sustained drug release from the larger pellet size could be attributed to either the lower surface area of the larger pellets compared to the smaller pellets or increased average distance for diffusion of the active ingredient from the pellet (33).…”
Section: Resultsmentioning
confidence: 99%
“…The MCC is not completely impeded within tablet matrix. However, interconnection bond after melting the lipid [27][28][29] and intragranular and intergranular bonds within the lipid while extruding the blends might occur [30]. Therefore, it can be concluded that this fusion bonding of MCC with the lipid while extruding made the MCC completely embedded within the matrix and prevented tablet splitting and burst release in the dissolution media, instead leading to the complete disintegration that occurred after 2 h in our case when MCC was not co-processed via HME with the rest of formulation components.…”
Section: Tablet's Excipient MCC Co-processed With Lipid To Improve Tamentioning
confidence: 99%
“…During the initial stage of the dissolution test, the drug clusters located on the surface of the granules were readily released into the dissolution medium. As the dissolution process progressed, fewer drug clusters were accessible to the dissolution medium, and a plateau was reached [29]. This plateau behavior was because the mixture was under the percolation threshold.…”
Section: In Vitro Release Study For the Screened Milled Extrudates Fomentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that the optimized formulation, was able to retard the drug release at the low pH and control it at intestinal pH, which makes it a promising colon-specific delivery system. Zhang et al [25] investigated the development a colon delivery system, using melt-extruded granules of mesalamine and Eudragit® FS. The developed product exhibited higher physical strength, smaller pore size and lower porosity compared with the conventionally prepared granules.…”
Section: Main Text Time Dependent and Ph Responsive Approachesmentioning
confidence: 99%